Antioxidant Effects of Methylcobalamin on Cerebellar Granule Cells (A 6 Week Quantitative Study in Albino Rats) (Medical Forum Monthly, 2021)
Objective: As there is deficient text on the regenerative capacity of Methylcobalamin on neuronal tissue therefore this original study was carried out to document its effects on granule cell degraded by lithium carbonate.Study Design: Observational Experimental studyPlace and Duration of Study: This study was conducted at the Animal House of Basic Medical Sciences Institute (BMSI) JPMC, Karachi from 1st June and ended at 14th July 2013.Materials and Methods: 15 male albino rats were selected weighing 195-200 grams and divided according to the treatment duration of the research was 6 weeks. Group A had 5 animals on lab diet, Group B consisted of 5 animals on lithium carbonate .Lithium carbonate (Adamjee pharmaceuticals) was given 25 mg/kg/day in saline once every day for six weeks. Group C had 5 animals on Injection Methylcobalamin (Amson vaccines and pharmaceuticals) 200 µgkg/day / intraperitoneally for 6 weeks.Results: Group C showed restoration of the number of granule cellsConclusion: Our present study proved that Methylcobalamin plays a vital role as an antioxidant vitamin